The Concept of Harm Reduction from Tobacco: Past, Present, Future - S. L. Babak; M. V. Gorbunova; A. G. Malyavin; I. V. Shashenkov (Архивъ внутренней медицины, 2021)
The concept of tobacco harm reduction (THR) is a speculative and controversial topic in the context of the international battle against the use of all types of tobacco. This concept involves providing tobacco users who are unable or unwilling to quit smoking or using other types of tobacco (snuff, chewing), with modified risk tobacco product (MRTP) for continued use. Skepticism about THR is huge and is associated with the negative experience of tobacco companies to produce cigarettes with a low content of tobacco tar/nicotine, which should have had significantly lower health risks than conventional cigarettes. Paradoxically, such an experience served as a springboard to an increase in the number of tobacco products that potentially have the properties of MRTP. Moreover, some members of the anti-smoking coalition, including WHO, consider the transition of tobacco smokers to MRTP as a strategy with great potential. However, the European Group of Experts believes that the MRTP strategy does not work and will lead to another generation of young people getting used to tobacco. In this article, we have critically analyzed the history of the past and present of tobacco products, myths and contradictions around them. We have tried to evaluate the modern concept of S THR as objectively as possible, which has a high potential for a real reduction in the number of deaths associated with smoking.